A+3sqrt BX+C = D solve for x

First subtract A and C from both sides. Leaving you with 3(sqrt(BX)) on one side and D-A-C on the other. then divide both by 3. sqrt(BX) = (D-A-C)/3. Then square both sides and divide by B. The result will then be

X = (D-A-C)^2/(9B)

Check your work by choosing A = B = C = 1 and D = 4

X = (4-1-1)^2/9 = 4/9 now plug this back into the original to prove that you didn't make a mistake

1 + 3sqrt(4/9) + 1 = 4

1 + 3*2/3 + 1 = 4

4 = 4 Looks like your solution checks out.